The Digital Route: Social Media Marketing Activies Impact on Bus Service Purchase Behavior - Roosdhani, Mohamad Rifqy; Arifin, Samsul; Ali, Ali; Komariyatin, Nurul (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
This study aims to identify the social media marketing tactics that bus service should employ to enhance their purchase decision, underscoring the need for these tactics to be complemented by involvement and promotion for optimal effectiveness. A quantitative methodology is utilized, involving data collection and analysis from a purposive sample of 506 respondent from PO. Bejeu Jepara’s clients. Data were gathered via questionnaires to assess the empirical model using Structural Equation Modeling (SEM-AMOS). The findings indicate that social media marketing activities positively and significantly influence purchase decisions when mediated by involvement and promotion. However, direct social media marketing activities do not show a significant impact on purchase decisions. This study offers fresh insights into the specific social media marketing activities that Bus Service should embrace. It underscores the pivotal role of Involvement and Promotion in enhancing the effectiveness of these strategies, leading to improved outcomes and stronger customer relationships.